THE EFFECTIVENESS OF JUDICIAL OVERSIGHT OF WIRETAPPING IN THE LAW ENFORCEMENT PROCESS - Gunawan Widjaja; Adrian Bima Putra (Jurnal Komunikasi, 2025)
Judicial oversight of wiretapping in the law enforcement process is an important aspect to maintain the integrity and credibility of the judiciary. This research aims to analyse the effectiveness of the Judicial Commission (KY) in carrying out its supervisory function through wiretapping actions against judges suspected of violating the code of ethics and conduct. The research method used is normative juridical with a qualitative approach, examining legislation, legal doctrine, and the results of previous research. The results showed that the effectiveness of judicial oversight of wiretapping is still not optimal, mainly due to KY's dependence on other law enforcement officials, the resistance of the Supreme Court, and limited regulations and resources. In addition, overlapping authorities and lack of synergy between institutions also hinder the effective implementation of wiretapping. This research recommends the need to strengthen KY's authority, revise regulations, and increase inter-agency collaboration to strengthen judicial oversight and maintain judicial integrity